Determinants of participation in community-based rehabilitation programmes among caregivers of disabled children - Mohd Said, Faridah (2012)
Caregivers’ participation in rehabilitation is an active involvement in an acceptable course of a rehabilitation intervention programme to produce a desired therapeutic outcome, prevent complications arising from the disability and eventually improve the quality of life (QOL) of children with disabilities. It involves elements of motivation to stay adhered throughout the process, in which the majority of clients do not. The Health Belief Model (HBM) postulates reasons for none adherence to rehabilitation programs closely related to lack of motivation, barriers to treatment and ineffective self-efficacy to perform the required health behaviour. Permanent disability acquired by children with disabilities (CWD) has negative social, financial and QOL implications. Caregiver need to stay at a high-level of participation within rehabilitation programmes in community-based rehabilitation centres (CBRC) in the course of QOL and importantly be inclusive in the community. The caregivers of CWD are an essential pillar to ensure full participation in the CBR programme. However, previous studies reported low participation to CBRC among caregivers which has long term negative implications for the CWD, their caregiver and the community. This study examined the determinant factors influencing caregivers’ participation in community-based rehabilitation programmes. The direct and mediating variables been explored. This is a correlation study with the HBM used as a research framework. Fourteen CBR centres were randomly selected using stratified random sampling. Data was collected using a self-administered questionnaire from 299 randomly selected caregivers from CBRC who met the inclusion criteria. Data analysis employed descriptive statistic, Paired T-test, ANOVA and Structural Equation Modeling (SEM) to examine direct and mediating variable to answer the research questions. The findings of the study showed that the average age of caregivers was 41.9 years. The largest proportions (36.5%) were among adults aged (40-49 years), and most are women (70.2%). The average age of CWD was 10.2 years. Finding revealed that more than one-fifth (22.7%) of the CWD are diagnosed as Cerebral Palsy, Down syndrome (21.4%), and over a quarter (25.8%) classified in other categories of disabilities. The majority of caregivers 59.5% revealed of low level of participation, while only 52.8% perceived that disability of the child in the low, "cues for actions" was low (53.2%). More than half of respondents (60.5%) perceived threat of disability, while 54.5% of them perceived benefit from the CBR and a total of 51.2% perceived barrier to be involved with the CBR. Cues to actions were statistically significant (p<0.05) determinative of caregivers participation in CBR in the range of moderate effect size. Findings of the test T-Test and ANOVA showed significant differences in severity of disability between gender, age, and differentiation of severity of disability before and after the intervention program CBR at p <0.05 with effect size from large to small depending on the disability domain. Results showed that younger age and gender have different results with a significant recovery. Structural equation modeling analysis (SEM) was conducted to test the proposed mediation model. The model shows a direct and mediation effect between the relationship perceived severity illness, cues for actions, coordinated care, implementation of care and self-efficacy with caregivers’ participation through perceived threat, perceived benefits and perceived barrier. This model showed a good fit to the data of the study (p<0.05, X2/df = 1.785, CFI = 0.909. IFI = 0.910 and RMSEA = 0.055). Further inspection revealed that result from SEM showed that cues for action has a direct effect on caregivers’ participation to CBR, while no significant mediation effect in relationship between participation with perceived severity, cues for actions, coordinated care, implementation of care through perceived threat, benefit and barrier. In conclusion, findings indicate that there is a direct effect of "cues for action" on caregiver participation in CBR. Caregivers’ perceived that CBR programme significantly reduced the severity of disability, thus, improved the quality of life of CWSN. Cost-effective strategies must be formulated to increase the participation among caregivers. Improve information through social support networks helps to enhance knowledge and self-efficacy to increase participation among caregivers. Implementation of the program should be coordinated to tailor with caregivers and CWD needs to overcome barrier and enhanced perceived benefit of participation. This study provides implications for CBR programme planner and providers with regards to the importance of information in enhancing participation.